Collaborative Online International Learning (COIL): Internationalization at Home (Journal of Parents and Teachers, 2025)
In this interview, we talk with Magdalena Custodio Espinar and Javier Pinilla Arbex, who share their perspectives on the COIL (Collaborative Online International Learning) model. Through their complementary experiences, the academic benefits, organizational challenges, and intercultural value that this methodology brings to both students and teachers are addressed. The dialogue offers an enriched vision of how international collaborative work transforms educational practices in digital and global contexts, promoting global training without the need for physical mobility.
Keywords: intercultural communication; online learning; international education; educative innovation; digital competence